(untitled) (American Journal of Pedagogical and Educational Research, 2022)
The research investigated the association between Lean Manufacturing (LM) and operational efficiency (OE) within the Nigerian manufacturing industry. A sample of one hundred (100) executives and managers from fourteen (14) purposively chosen manufacturing firms in Nigeria participated. The study utilized a quasi-experimental research configuration and embraced a cross-sectional questionnaire for data gathering. The Statistical Package for Social Sciences (SPSS) Version 25 was employed for data analysis, using the structural equation modeling (SEM) via the AMOS software. The results reveal a robust positive and significant correlation between lean manufacturing (LM) and operational efficiency (OE) within the Nigerian manufacturing industry. Specifically, the result of data analysis revealed a robust positive and significant association between leanness and the measures of operational efficiency (quality of output and delivery time/pace) respectively within the Nigerian manufacturing industry. Similarly, the research also revealed a robust positive and significant correlaion between waste reduction and the measures of operational efficiency (quality of output and delivery time/pace) respectively within the Nigerian manufacturing sector. In light of these findings, the study concludes that leanness and waste reduction play significant roles in enhancing quality of output and delivery time/pace respectively within the Nigerian manufacturing sector. The theoretical and managerial implications of these findings were also discussed.